Risk Scoring System for Vancomycin-Associated Acute Kidney Injury - Kim, Jee Yun; Kim, Kyun Young; Yee, Jeong; Gwak, Hye Sun (Frontiers in Pharmacology, 2022)
Vancomycin-associated acute kidney injury remains a major challenge for patients and clinicians. This study aimed to construct a risk scoring system for vancomycin-associated acute kidney injury. We retrospectively reviewed medical records of patients who underwent therapeutic drug monitoring for vancomycin from June 2018 to July 2019. We selected possible risk factors for acute kidney injury by univariate and multivariable logistic regression analyses and developed a scoring system for vancomycin-associated acute kidney injury. Machine learning methods were utilized to predict risk factors for the occurrence of acute kidney injury. The incidence of vancomycin-associated acute kidney injury was 31.7% among 104 patients included in this study. A bodyweight ≤ 60 kg (2 points), a Charlson comorbidity index ≥ 3 (2 points), a vancomycin trough serum level > 15 µg/mL (1 point), and concomitant use of ≥ 6 nephrotoxic agents (2 points) were included to construct a risk scoring system based on the coefficient from the logistic regression model. The area under the receiver operating characteristic curve (mean, 95% confidence interval) across 10 random iterations using five-fold cross-validated multivariate logistic regression, elastic net, random forest, support vector machine linear kernel, and support vector machine-radial kernel models was 0.735 (0.638–0.833), 0.737 (0.638–0.835), 0.721 (0.610–0.833), 0.739 (0.648–0.829), and 0.733 (0.640–0.826), respectively. For total scores of 0–1, 2–3, 4–5, 6–7, the risk of vancomycin-associated acute kidney injury was 5%, 25%, 45%, and 65%, respectively. Our scoring system can be applied to clinical settings in which several nephrotoxic agents are used along with vancomycin therapy.